Living Mission Interculturally : Faith, Culture, and the Renewal of Praxis - Gittins, Anthony J., 1943- (Book collections on Project MUSE., 2015)
Our globalized world increasingly brings together people of many different cultures, though not always harmoniously. In recent decades, multinational companies have sought more efficient strategies for authentic intercultural collaboration. But in today's multicultural world-church, faith communities too -- from local parishes to international religious communities -- are faced with the challenge of intercultural living. The social sciences have developed some constructive approaches, but people of faith also need to build their endeavors on a sound biblical and theological foundation. Living Mission Interculturally integrates sociology/anthropology with practical theology, reminds us that good will alone is not enough to effect change, and points to a way of intercultural living underpinned by faith, virtue, and a range of new and appropriate skills.